Language Acquisition on Students Who Experience the Speech Delay - Wahidy, Achmad; Effendi, Darwin; Wardiah, Dessy; Riyanto (UNIB Press, 2024)
The acquisition of language in children is one of the greatest and most amazing human achievements, which is why this problem has received great attention for analysis. Language acquisition and speaking are both interrelated aspects. Talking is the most effective form of communication. Aspects of biological maturity, and cognitive and social environment affect the acquisition of children's language and speaking abilities. However, not all children have good language development, some children experience disturbances in their biological aspects so that the acquisition of language and speech is delayed. These problems are interesting for further analysis related to the factors of language development in children with (speech delay). The research findings indicate that several words were mispronounced, leading to information that did not match the child’s intended meaning based on the observations and interviews that the researchers conducted during the study. The study revealed that toddlers with speech impairments had trouble pronouncing and articulating words clearly. Even simple words in daily activities at home were shaky in some cases. Researchers can also draw the conclusion that, despite the fact that the child interacts often with parents, relatives, and neighbors in their social milieu, the youngster nonetheless exhibits speech difficulties. This is a result of the child's frequent inability to articulate the thoughts that are going through his mind, even in a single sentence.